STATEOF KIDNEYS VASCULAR ENDOTHELIUM AND SYSTEMIC ENDOTHELIUM DYSFUNCTION OF VESSELS IN PATIENTS WITH HENOCH-SCHÖNLEIN PURPURA - Syniachenko, O.V.; Bevzenko, T.B.; Diadyk, O.O.; Iermolaieva, M.V.; IegudinaЕ.D.; Suiarko, VI. (Ukrainian Journal of Nephrology and Dialysis, 2016)
Purpose – to assess the nature of the vascular endothelium dysfunction in henoch–schonlein purpura (HSP) with glomerulonephritis (GN), its pathogenetic importance, the degree of change arteriole endothelium and immune deposits in the glomerular endothelium cells of the kidneys, and their relationships. Material and methods. The study included 82patients with HSP, among which in 21 cases of GN in vivo reserash of kidney tissue was accomplished, including the degree of immune complexes deposits in the endothelial cells were studied. Indicators of vascular endothelium function were compared with blood levels of immune-inflammatory proteins and the nature of the adsorption-rheological properties of serum. The state of changes in blood vessels of the kidneys and the immunoglobulin’s (Ig) A, G, Mlevel ofdeposits in the glomerular endothelium cells, C3- and Clq-components ofcomplement were assessed. Results and discussion. HSP is accompanied by increase in blood the level of endothelin-1, thromboxane-A2 and cyclic guanosine monophosphate against a background of decrease the amount of prostacyclin and nitrite, which is related to the total level of disease activity and severity of kidney damage, with the parameters of fibrinogen, 2-microglobulin, IgA, IgG, IgM, rheumatoid factor and circulating immune complexes in blood, as well as surface tension, viscoelasticity modulus, surface and volumetrical viscosity of serum. The level of thromboxanemia determines the severity of vessels’elas- tofibrosis and the indices of cyclic guanosine monophosphate - the degree of proliferation of the arteriolar endothelium and the deposits of IgG in the glomerulus’endotheliocyte. Conclusions. Expressed disturbances of vessels’ endothelium function peculiar to HSP, that is determined by the activity of the disease and the severity of GN, correlated with blood levels of immune-inflammatory proteins and the disorders of adsorption-rheological properties of serum, the affection of the endothelium of arterioles of the kidneys and increase in the deposition of immune complexes in the glomerulus’endotheliocytes.